REVOLUTIONIZING HEALTHCARE ACCESS: "THE TRANSFORMATIVE ROLE OF SPACE TECHNOLOGY IN TELEMEDICINE AND TELEHEALTH" - Ms. Anwesha Pathak *Dr Rajlakshmi Wagh (Chelonian Research Foundation, 2024)
Space-based satellite communication systems shall provide reliable, high-speed internet connectivity to remote and rural areas where traditional infrastructure is lacking. This connectivity is extremely essential for real-time video conferencing, data transfer, and remote consultations between healthcare providers and patients. In remote or isolated regions, where access to healthcare facilities is limited, satellite communication will enable telemedicine consultations. Patients will be able to connect with healthcare professionals and receive medical advice or even treatment remotely. In medical emergencies in remote areas, satellite communication shall ensure that healthcare providers can consult with specialists in real-time, improving the quality of care provided. Space technology, including satellites and wearable devices, will allow for the remote monitoring of patients' vital signs and health data. The author in this paper shall focus on how space technology shall help to support global health initiatives by tracking the spread of diseases and monitoring healthcare infrastructure in remote regions. This data aids in the planning and delivery of healthcare services. Keywords: Telemedicine, Telehealth, remote sensors, space technology, satellites.